Awareness of oral cancer and potentially malignant oral disorder among final year medical and dental undergraduate students of Chitwan Medical College, Nepal - Subedi, Sushil; Shrestha, Bijayata (Journal of Chitwan Medical College, 2019)
Background: Oral Cancer (OCA) is a common malignancy in South East Asia and the burden of the disease is increasing. OCA is usually preceded by Potentially Malignant Oral Disorder (PMOD). The early detection of these diseases may limit the high mortality and morbidity. The objectives of this study were to assess the awareness of burden, associated risk factors, early detection and prognosis of OCA and OPMD among final year medical and dental students.. Methods: This cross sectional study was conducted among final year Medical and Dental undergraduate students of Chitwan Medical College, Nepal in April 2017 using a pre tested self-administered questionnaires. All the final year students present at their respective classes (Dental= 50 and Medical=75 students) responded to the questionnaires after giving informed consent. Data entered in SPPS 20 software was analyzed using Pearson Chi Square test and Fisher exact test. Results: Dental students had better awareness concerning PMOD. Yet, the dental students did not differ significantly from their medical counterpart in most of the responses related to OCA. Surprisingly, more Dental students had misconception that OCA is not preventable and early detection is difficult. Few of both groups were confident in having sufficient knowledge in OCA prevention and detection. Only 18.6% of Medical students had examined PMOD and few students of both groups had examined OCA. Conclusions: This study revealed the deficient aspect in the knowledge concerning OCA and OPMD among Medical and Dental students indicating the need to emphasize on these aspects of medical education.